The Effect of Green Accounting Implementation, Sales Growth, and Firm Size on Firm Value (A Study on Consumer Goods Industry Companies Listed on the Indonesia Stock Exchange (IDX) in 2019–2023) - Sabriyanti, Nabila; Romli, Romli (CV. Proaksara Global Transeduka, 2025)
This research examines how environmental accounting practices, revenue expansion, and company scale affect corporate valuation. The researchers employed a quantitative approach using associative causal analysis. Through purposive sampling, they selected 22 consumer goods companies trading on the Indonesian Stock Exchange from 2019 to 2023, generating 110 data observations. The findings reveal that environmental accounting practices alone do not impact corporate value. However, revenue growth and company size both demonstrate positive and statistically significant effects on firm valuation. When examined together, all three factors collectively influence corporate value in a meaningful way. These findings offer valuable insights for investment professionals and corporate executives when making strategic decisions that balance environmental sustainability considerations with financial performance objectives.